2013
DOI: 10.1016/s1836-9553(13)70142-5
|View full text |Cite
|
Sign up to set email alerts
|

Preventive exercises reduced injury-related costs among adult male amateur soccer players: a cluster-randomised trial

Abstract: NTR2416.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
55
1
8

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 25 publications
0
55
1
8
Order By: Relevance
“…Cost differences in favour of the intervention group were reported per player (mean difference €201, 95% CI €15 to €426) and per injured player (mean difference €350, 95% CI €51 to €733) 23. Krist et al 23 used ICERs and cost-effectiveness planes, however exposure hours were not considered, limiting the comparability of results to this study.…”
Section: Discussionmentioning
confidence: 94%
“…Cost differences in favour of the intervention group were reported per player (mean difference €201, 95% CI €15 to €426) and per injured player (mean difference €350, 95% CI €51 to €733) 23. Krist et al 23 used ICERs and cost-effectiveness planes, however exposure hours were not considered, limiting the comparability of results to this study.…”
Section: Discussionmentioning
confidence: 94%
“…9,35 Strategies to prevent hamstring injuries, such as the NHE, may reduce the incidence of hamstring injury, medical costs, and personal suffering of the injured player. 26,29,33 Although previous studies in professional soccer have shown promising results, differences between professional and amateur soccer players in medical staff, level of play, training exposure, training intensity, and compliance to preventive measures have to be considered. Therefore, the findings for professional players cannot be extrapolated to amateur soccer players.…”
mentioning
confidence: 99%
“…Por el contrario, registros más bajos respecto de la estabilidad postural indican mayores riesgos de lesiones articulares (McGuine & Keene, 2006;Plisky et al, 2006). Algunos investigadores además de incidir en el programa propioceptivo como elemento fundamental en la prevención de lesiones y mejoras en la estabilidad, inciden en el entrenamiento de otras áreas como puede ser el entrenamiento de fuerza de la musculatura insertada en las articulaciones, el entrenamiento coordinativo, el entrenamiento de la musculatura del cinturón lumbo-pélvico (Krist, van Beijsterveldt, Backx, & de Wit, 2013;Mandelbaum et al, 2005;O'Driscoll, Kerin, & Delahunt, 2011). Esto indica que no solo gracias al entrenamiento a nivel propioceptivo se consiguen mejoras a nivel de estabilidad en la articulación y como consecuencia de ello reducción de lesiones deportivas en las mismas, sino que la implementación de otros tipos de contenidos, como lo que se exponen anteriormente, facilitan la consecución del éxito de los programas preventivos articulares (Alentorn-Geli et al, 2009;Chappell & Limpisvasti, 2008;Gilchrist et al, 2008).…”
Section: Discussionunclassified